Epidemiological manifestations of tuberculosis infection in the Omsk region: dynamics and trends - I. V. Kostyukova; O. A. Pasechnik; I. V. Mokrousov (Acta Biomedica Scientifica)
Background. Tuberculosis (TB) infection remains relevant as one of the leading public health problems in Russia.The aim. To characterize the dynamics and trends of epidemiological manifestations of TB infection in the Omsk region.Materials and methods. An observational descriptive-evaluative epidemiological study was carried out in the Omsk region from 2009 to 2021. The data available in the Federal statistical observation forms NN 7, 8, and 33, and results of the bacteriological study of patients with respiratory TB were analyzed.Results. In the Omsk region, an improvement in the epidemiological situation was observed from 2009 to 2021. It was associated with a decrease in TB prevalence by 3.7 times (from 325.6 to 86.7), mortality – by 5.8 times (from 21.1 to 3.6), incidence – by 2.7 times (from 130.7 to 48.4 per 100,000). At the same time, proportion of microscopy/culture-positive patients infected with multidrug-resistant Mycobacterium tuberculosis strains increased from 9.2 to 29.8 % among all patients, and from 15.5 to 30.6 % among newly diagnosed patients. There was a trend towards an increase in the number of cases with primary extensive drug resistance of M. tuberculosis. The incidence of tuberculosis associated with HIV infection has increased 10 times and reached 15.6 per 100,000 population.Conclusions. In the Omsk region, there is a change in the structure of M. tuberculosis strains with a predominance of multiple and extensive drug resistance along with decrease in TB incidence and mortality. New approaches are needed to organize the system of epidemiological surveillance and control of TB infection.